Pengujian Kekuatan Tarik Komposit Serat Kayu Mahoni Tanpa Pengaruh Alkali - Yanhar, M Rafiq; Siagian, Parulian (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2023)
Composite is defined as a combination of two types of materials, namely matrix and reinforcement which have different properties. Composites have the advantage that they are resistant to corrosion and also have good strength and stiffness. This study aims to determine the tensile strength of mahogany fiber composites without alkali, with variations in fiber volume of 10%, 30%, 50%, and variations of mesh 30, 50, and 80. The reinforcing particles are made in powder form by means of a blender with a matrix. BQTN 157 EX polyester resin was used. The results showed that the highest tensile strength was found in the mesh 80 experiment of 43.07 MPa. This shows that the smaller the composite reinforcing particles, the greater the tensile strength. While the smallest tensile strength is at 10% fiber volume, namely 14.21 MPa. Tensile strength reaches its maximum at 30% fiber volume, which is 32.76 MPa. The addition of fiber volume to 50% actually lowers the tensile strength to 20.69 MPa.